Typologies of activity-related behaviours during adolescence and their transitions: a longitudinal analysis of the ELSPAC cohort - Janda, David; Gába, Aleš; Contardo Ayala, Ana María; Timperio, Anna; Andrýsková, Lenka; Piler, Pavel; Arundell, Lauren (BMJ open, 2024)
OBJECTIVES: The objective of this study was to identify typologies of activity-related behaviours during adolescence and to explore transitions between the identified typologies. Additionally, we aimed to identify demographic indicators associated with the transitions and typology membership. DESIGN: Prospective cohort study. SETTING: Czech Republic. PARTICIPANTS: Individuals involved in the Czech part of the European Longitudinal Study of Pregnancy and Childhood study, aged 11 to 18 years. The study involved over 563 individuals, of whom 380 provided complete data for the analysis. PRIMARY OUTCOME MEASURES: Time spent outdoors, participation in organised physical activity (PA) and sport activities, time spent watching television and using a personal computer, and total sleep duration at ages 11, 15 and 18 years. Typologies were identified using Latent Transition Analysis. RESULTS: Four typologies of activity-related behaviours were identified and labelled to reflect their behavioural profiles: (1) Actives (high outdoor time and organised PA and sport participation, low screen time and optimal sleep duration); (2) Active screeners (median outdoor time, high organised PA and sport participation, high screen time, and optimal sleep duration); (3) Poor sleepers (average outdoor time and organised PA and sport participation, low screen time and not meeting sleep guidelines) and (4) Averages (average duration of all behaviours and optimal sleep duration). A major shift in typology membership from 11 to 18 years was observed, with a decreasing proportion of individuals in typologies characterised by a high proportion of outdoor time and participation in organised PA and sport activities (ie, Actives; Active screeners). A high proportion of individuals also transitioned to the typology with poor sleeping habits (ie, Poor sleepers). Sex and maternal education were associated with the typology membership and transition probabilities (p<0.05). CONCLUSIONS: Targeting lifestyle interventions to those with specific lifestyle patterns in early adolescence may be beneficial for reducing the risk of poor sleep and promoting healthy lifestyle patterns later in life.
Keywords: Female; Exercise; Adolescent; Sports; Sedentary Behavior; mužské pohlaví; čas strávený před obrazovkou; Screen Time; longitudinální studie; prospektivní studie; Humans; Adolescent Behavior; zdravé chování; Prospective Studies; Longitudinal Studies; Czech Republic; cvičení; chování mladistvých; spánek; lidé; PUBLIC HEALTH; Sleep; ženské pohlaví; Child; sporty; Česká republika; sedavý životní styl; dítě; Health Behavior; Male; mladiství